Human Resource Management Strategies for Enhancing Kindergarten Teacher Professionalism: A Multisite Study at PGRI 4 Kindergarten and Muslimat NU 10 Khodijah Kindergarten, Bangil - Novi Sulistiyorini; Taufiq Harris; M. Furqon Wahyudi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Teacher professionalism is a key determinant of the quality of early childhood education services. Enhancing teacher professionalism depends not only on individual competencies but also on the human resource management (HRM) strategies implemented by educational institutions. This study aims to analyze HRM strategies for improving teacher professionalism, identify the factors influencing their implementation, and develop a strategic HRM model for kindergarten institutions. A qualitative approach with a multisite research design was employed at PGRI 4 Kindergarten Bangil and Muslimat NU 10 Khodijah Kindergarten Bangil. Data were collected through in-depth interviews, participant observation, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing through cross-site analysis. The findings reveal that HRM strategies are implemented through five major stages: teacher workforce planning, competency-based recruitment, continuous professional development, performance supervision and evaluation, and the provision of motivation and rewards. These strategies have contributed to improving teachers' pedagogical, professional, social, and personal competencies. Supporting factors include effective school leadership, a collaborative organizational culture, teachers' commitment, and support from the governing organization. Conversely, limited financial resources, unequal access to professional training opportunities, and excessive administrative workloads remain significant barriers. This study proposes a Sustainable Integrative Human Resource Management Strategy Model that integrates workforce planning, competency development, academic supervision, performance evaluation, and a reward system into a continuous cycle for enhancing kindergarten teachers' professionalism.